Macular surgery - Quiroz-Mercado, Hugo.; Kerrison, John B. (Philadelphia : Wolters Kluwer/Lippincott Williams & Wilkins Health, 2011)
"The second edition of Macular Surgery has been completely rewritten to reflect diagnostic and therapeutic point of view. Macular surgery has been most dramatically impacted by the development of smaller instrumentation allowing surgery to be performed more rapidly and with less morbidity. The continued advancement of ocular coherence tomography has allowed the surgeon greater insight into diseases of the vitreo-macular interface including macular hole, epiretinal membrane, and vitreo-macular traction"--Provided by publisher.
section 1. Anatomy and pathophysiology of the macula -- section 2. Imaging of the macula -- section 3. Surgical techniques -- section 4. Diabetic retinopathy -- section 5. Macular edema -- section 6. Vitreous traction maculopathies -- section 7. Macular holes -- section 8. Choroidal neovascularization and age-related macular degeneration -- section 9. Infectious diseases of the macula, pediatrics, and trauma -- section 10. Miscellaneous and tumors -- section 11. Prevention and treatment of complications -- section 12. Frontiers in macular surgery.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2022. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Macula lutea -- Surgery; Electronic books